Phenomenological Study: Women's Adjustment in Early Marriage Decisions - Mercia Chusumi Maulina; Asri Rejeki (Philanthropy: Journal of Psychology, 2024)
Abstract. Early marriage is still a phenomenon in the neighborhood. Several factors cause someone to marry early. The purpose of this study is to give the readers an insight into a woman's adaptation in deciding the marriage age so that later, the number of early marriages can be indirectly reduced. The research method used is qualitative research based on the philosophy of postpositivism. Data collection techniques are triangulated (combined), and data analysis is inductive/qualitative. Data will be collected using in-depth interview techniques and documentary studies. In this case, researchers will study 3 women who marry at an early age. The results of this study show that most of the factors that cause early marriage are encouragement from parents and economic factors. The study results can describe self-adjustment in women who married early to get better.Keywords: Self-Adjustment; Early Marriage; Women; Decision Making